Measuring of positioning, circularity and static errors of a CNC vertical machining centre for validating the machining accuracy - Usop, Z.; Sarhan, A.A.D.; Mardi, N.A.; Wahab, M.N.A. (Flow Measurement and Instrumentation, 2015)
A CNC machine tool performance depends on the machine accuracy status which is very important to determine the end product compliance to the specification. The accuracy of the machine can be measured and analyzed; hence the errors' impact can be predicted on a workpiece. This paper presents three types of accuracy tests performed on a CNC Vertical Machining Centre, how the accuracy status affect the end product quality and what are the corrective actions to be taken. First, the laser test to determine the linear positioning accuracy, second the ball bar test to determine the circularity accuracy and third, the static accuracy test to determine the machine current static accuracy status and finally the cutting test to determine the actual machine accuracy effect on a work piece. Machine tool's errors can be diagnosed and minimize or eliminated by either electronic compensation or mechanical maintenance and sometimes both need to be done. (C) 2014 Elsevier Ltd. All rights reserved.